Solidão e reinvenção: a experiência da maternidade após a separação conjugal - Pereira, Valéria Brandão (2018)
This work aims to analyze and understand the experience of maternity for separated mothers who live with their children. It is justified by the increasing number of conjugal separations in the present, which imply in the reorganization of the family and in the development of new forms of parenthood. This is a qualitative research, which used semi-structured interviews as a means of knowing and understanding the personal experiences of the mothers interviewed. Specifically, this study aimed: a) to learn how separated mothers perceive the exercise of motherhood after marital separation; b) to know, from the mothers' report, the relationship between mothers and children after the marital separation; c) to investigate, from the mothers' report, the relationship between separated mother and her ex-partner, considering the permanence of the parental bond between them. The research was based on family studies, as well as on the theoretical contribution of Donald W. Winnicott, which allows thinking the motherhood as a psychosocial process, inseparable from the relational and sociocultural environment in which women are inserted. The 6 participants were found in the age group from 25 to 37 years old, with school level between high school and university. The mothers were separated for less than 5 years, with 1 or 2 children, who had ages between 1 and 13 years. Half of the participants were the main provider of the family, while the others stated that they were financially dependent on their families of origin. The results show that marital separation is a complex experience that affects the exercise of motherhood, producing suffering and vulnerability, as well as possibilities for emotional development. Solitude and freedom led these women to greater responsibilities, dedication, and attachment to their children, searching for personal autonomy. It was observed that mothers often have a furtherance network made up of family members, friends or neighbors, acting as important financial support, emotional and sharing care for their children. The study suggests the expansion of the holding possibilities of the psychosocial environment, through policies and assistance programs that support mothers, especially the less educated and the poorest. The need for other studies on the subject is emphasized, allowing a deeper understanding of the impacts of the marital separation on the experience of parents, mothers, and children in this context.